Judicialização da política pública: o diálogo como forma de concretização da saúde preventiva - VELOSO, Marcelene Dias da Paz (Universidade Federal do Pará, 2017)
This dissertation analyzes the field of action of the Judiciary and its limitations within the demands made upon the Public Administration, regarding the development, implementation and evaluation of the public policies for the provision of preventive health care services with an emphasis on the ‘Health and Family Program’. The analysis highlighted the main obstacles mentioned in the doctrine and in the jurisprudence with regard to the implementation of the fundamental rights by means of judicial proceedings. To this end, the study identified the main problems that have arisen during the implementation of preventative health care services carried out due to judicial proceedings by collating the social demands with resource constraints. The study also suggests a possible approach to overcome the tensions among the constituted powers by resorting to examples of practices from other countries such as institutional dialogue, which guarantees the enjoyment of the fundamental rights set out by the Brazilian Constitution. The ‘Health and Family Program” of the federal government was herein analyzed due to fact that it comprises most of the policies on the provision of preventive primary health care services on the one hand and most of the judicialization cases on the other hand. The analysis herein issued, demonstrates that the Judiciary can contribute to the improvement of health public policies. The dissertation also brings an analysis of a judicial proceeding concerning the provision of Human Papiloma Virus (HPV) vaccine. Finally, it also comprises a research carried out in the Federal Supreme Court during the period of 2010-2013, which aimed at identifying judicialization cases in the provision of preventive health care services then processed and judged in the Court.